(untitled) (Scientific journal of the Fergana State University, 2023)
This article highlights the problem of a systematic approach to identifying linguistic features of the properties of poetic speech, outlines opinions regarding the criteria of poetic phonetics, poetic vocabulary, morphology and syntax. Provides information on the linguistic properties of poetic speech.